Estandarización y optimización de parámetros para la elaboración de helado de crema de leche con adición de almidón de achira (Cana indica) como estabilizante en ciudad de Loja - Jaramillo Puertas, César Oswaldo (2012)
The present investigation executed it in the laboratories of the plant of production of the Technological Top Institute "Daniel Álvarez Burneo" located in the Av. Shores of the Zamora and the street Juan of Salt mines, in the parish the Valley of the Canton Loja Loja's province, to 1.220 m.s.n.m. of altitude, the Investigation had a duration of 30 days. he raised aims were a) To determine the ideal percentage of starch (1 % 2 % and 3 %) of Achira (canna indicates) as estabilizante in the production of the ice cream of cream of milk b) To establish the best treatment by means of the evaluation of characteristics organolépticas by means of a leaf of catación c) To effect microbiological analyses to the best treatment d) chemists To realize physical analysis - to the best treatment e) To obtain the costs of the best treatment on having used starch of achira. I use 72 samples. The evaluated treatments consisted of variations of the proportion of milk starch of achira and cream of milk in the form bases of T1 (70%Milk) + (1%Almidon Achira) + (25%Crean of Milk, T2 (70%Milk) + (1%Almidon Achira) + (30%Crean of Milk, T3 (70%Milk) + (2%Almidon Achira) + (25%Crean of Milk, T4 (70%Milk) + (2%Almidon Achira) + (30%Crean of Milk, T5 (70%Milk) + (3%Almidon Achira) (25%Crean of Milk, T6 (70%Milk) + (3%Almidon Achira) (30%Crean of Milk, T7 (75%Milk) + (1%Almidon Achira) (25%Crean of Milk, T8 (75%Milk) + (1%Almidon Achira) (30%Crean of Milk, T9 (75%Milk) + (2%Almidon Achira) + (25%Crean of Milk, T10 (75%Milk) + (2%Almidon Achira) (30%Crean of Milk, T11 (75%Milk) + (3%Almidon Achira) (25%Crean of Milk, T12 (75%Milk) + (3%Almidon Achira) (30%Crean of Milk). A design was applied completely at random, with twelve treatments and six repetitions. To establish the best treatment I realize by means of a leaf of catacion to establish the statistical differences between the averages of the treatments, there was applied Tukey's test (P> 0.05). I realize the analyses physicist - chemical and microbiological of the best treatment T10 (75%Milk) + (2%Almidon Achira) (30%Crean of Milk). I determine the relation benefit / cost of twelve treatments in study, having that existed significant difference in his costs, determining that the tratamiento T12 (75%Milk) + (3%Almidon Achira) (30%Crean of Milk) T10 (75%Milk) + (2%Almidon Achira) (30%Crean of Milk and T8 (75%Milk) + (1%Almidon Achira) (30%Crean of Milk), has a relation benefit / cost of 5.74 $, 5.94 $ and 6.14 $ respectively been the best treatment T10 inside that Achira has the major indexes of benefit / cost and the treatments T3 (70%Milk) + (2%Almidon) + (25%Crean of Milk and T5 (70%Milk) + (3%Almidon Achira) (25%Crean of Milk) those who had the worst index benefit / cost that it are 0.08 $ and-0.06 respectively.